Suppressing temperature-dependent embrittlement in high-strength medium-entropy alloy via hetero-grain/precipitation engineering. (May 2023) - Chou, T.H.; Li, W.P.; Chang, H.W.; Cao, B.X.; Luan, J.H.; Huang, J.C.; Yang, T.
Abstract: Hetero-grain/precipitation engineering was adopted to improve mechanical properties of alloy over a wide temperature range. Partial recrystallization and L12 nanoprecipitation were simultaneously introduced into a CoCrNi-based medium entropy alloy, resulting in a heterogeneous microstructure. This kind of heterostructured alloy achieves an ultrahigh tensile strength of 1.5 GPa at 500 °C, and still maintains a tensile strength above 1.1 GPa at 600 °C. All elongations exceed 20% at −196 °C and elevated temperatures up to 700 °C, which indicates the breakthrough in temperature-dependent embrittlement encountered by many structural materials with equiaxed grain structures. Such a superior combination of strength and ductility at elevated temperatures can be ascribed to the stable deformed grains and pronounced planar defects, including stacking fault networks and deformation twins. This work demonstrates that hetero-grain/precipitation engineering can provide an effective strategy to achieve high strengths of alloys without sacrificing ductility over an extended temperature range. Graphical abstract: Image, graphical abstract